2013
DOI: 10.3201/eid1909.121846
|View full text |Cite
|
Sign up to set email alerts
|

Powassan Meningoencephalitis, New York, New York, USA

Abstract: Disease caused by Powassan virus (POWV), a tick-borne flavivirus, ranges from asymptomatic to severe neurologic compromise and death. Two cases of POWV meningoencephalitis in New York, USA, highlight diagnostic techniques, neurologic outcomes, and the effect of POWV on communities to which it is endemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…46 Powassan virus causes rare sporadic cases of neurologic disease in humans. In the United States, Powassan virus has been reported in the northeastern and north central states.…”
Section: Flaviviridaementioning
confidence: 99%
See 1 more Smart Citation
“…46 Powassan virus causes rare sporadic cases of neurologic disease in humans. In the United States, Powassan virus has been reported in the northeastern and north central states.…”
Section: Flaviviridaementioning
confidence: 99%
“…In the United States, Powassan virus has been reported in the northeastern and north central states. 46 Symptoms of infection vary from mild fever and myalgia to acute flaccid paralysis, encephalitis, and death. 46,47 …”
Section: Flaviviridaementioning
confidence: 99%
“…In a Lyme disease–endemic area, POWV seroreactivity and confirmed POWV infection were present. The spectrum of disease is broader than previously realized, with most patients having minimally symptomatic infection ( 1 , 10 , 11 ). Further studies are needed to characterize clinical disease of POWV monoinfection, document POWV seroprevalence in humans, and monitor epidemiologic trends.…”
Section: Discussionmentioning
confidence: 93%
“…Using these assays, investigators have identified ≈100 cases of POWV encephalitis; however, the actual incidence is likely higher ( 1 , 6 ). Although nonneuroinvasive disease has been described for other arboviral illnesses, our knowledge of POWV has been limited to patients with neuroinvasive disease ( 1 , 8 , 10 , 11 ). In this study, we evaluated the seroreactivity for POWV in US Midwest patients, many of whom did not have neuroinvasive disease.…”
mentioning
confidence: 99%
“…Following POWV infection, several long‐term sequelae were reported across 28 studies. The most commonly noted persistent symptoms were neurological issues (10/28), generalized weakness (7/28 studies), cognitive difficulties (7/28), speech difficulties (7/28), imbalance and difficulty walking (7/28) spastic quadriplegia (4/28), ophthalmoplegia (4/28) and headaches (4/28) (Camfield, Mehrmanesh, & Embil, ; Cavanaugh et al., ; Conway & Rossier, ; Courtney et al., ; El Khoury, Camargo, White, et al., ; El Khoury, Hull, et al., Fitch & Artsob, ; Gholipour, Thon, Bevers, Henderson, & Feske, ; Goldfield et al., ; Granger et al., ; Harrison et al., ; Hicar, Edwards, & Bloch, ; Hinten et al., ; Jackson, ; Lessell & Collins, ; Mahdy et al., , ; Mittal, Hassan, Sanchez, & Robertson, ; Partington, Thomson, & O'Shaughnessy, ; Piantadosi et al., , ; Raval et al., ; Shah & Elkhoury, ; Smith et al., ; Sung et al., ; Trépanier et al., ; Tutolo et al., ; Wilson et al., ). Various combinations of symptoms have been reported from both adults and children diagnosed with POWV and there does not appear to be case attributes that would aid in predicting symptoms or severity of POWV disease.…”
Section: Resultsmentioning
confidence: 99%